2015
DOI: 10.1002/2014ef000281
|View full text |Cite
|
Sign up to set email alerts
|

The global land rush and climate change

Abstract: Climate change poses a serious global challenge in the face of rapidly increasing human demand for energy and food. A recent phenomenon in which climate change may play an important role is the acquisition of large tracts of land in the developing world by governments and corporations. In the target countries, where land is relatively inexpensive, the potential to increase crop yields is generally high and property rights are often poorly defined. By acquiring land, investors can realize large profits and coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 75 publications
(134 reference statements)
0
26
0
1
Order By: Relevance
“…A pesar del crecimiento poblacional, el incremento proyectado de la productividad agrícola para aumentar la producción de alimentos en un 70 % para el 2.050, se proyectan mejoras en la seguridad alimentaria (Ghose 2014). El cambio climático tanto histórico como anticipado interactúa sustancialmente con los impulsores de las adquisiciones de tierras, ya que existe evidencia significativa de un efecto (negativo) de la pobreza asociado con la falta de acceso a los alimentos (Davis, 2015). Este planteamiento, permite de manera contextual introducirnos a los resultados obtenidos en la investigación.…”
Section: Resultsunclassified
“…A pesar del crecimiento poblacional, el incremento proyectado de la productividad agrícola para aumentar la producción de alimentos en un 70 % para el 2.050, se proyectan mejoras en la seguridad alimentaria (Ghose 2014). El cambio climático tanto histórico como anticipado interactúa sustancialmente con los impulsores de las adquisiciones de tierras, ya que existe evidencia significativa de un efecto (negativo) de la pobreza asociado con la falta de acceso a los alimentos (Davis, 2015). Este planteamiento, permite de manera contextual introducirnos a los resultados obtenidos en la investigación.…”
Section: Resultsunclassified
“…According to Resosudarmo et al (2014) [84], sustainable land use alternatives other than commercial farming, such as reducing emissions from deforestation and forest degradation, and fostering conservation and enhancement of forest carbon stocks (REDD+) should be considered, especially in those ecologically fragile areas where the threat of desertification is surging [85]. However, a study by [86] shows that through these carbon credit mechanisms (e.g., reducing emissions from deforestation, forest degradation, and REDD+), land-intensive policies may further heighten the demand for land. It has been suggested that it is time to move beyond the approach of internalizing externalities through payments for ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for investing in flexible crops is due to the fact that investors can easily switch between, food and biofuel uses, depending on end-market price differentials, thereby enabling producers to hedge against market fluctuations ( Schoneveld, 2014 ). Moreover, the investors' interest in these crops is also associated with the rise in demand for first-generation biofuels, mainly driven by binding European energy and climate targets ( Davis et al, 2015b;Antonelli et al, 2015 ). Carroccio et al (2016) shows that investments pursued by EU Member States are mainly driven by the need to reduce the energy deficit in view of the achievement of the objectives set out in the "Europe 2020".…”
Section: Scope: Flexible Crops Crops For Food and Crops For Energymentioning
confidence: 99%